Elevated intracellular calcium in neutrophils in patients with Down syndrome - Yamato, Fumiko; Takaya, Junji; Yasuhara, Akihiro; Teraguchi, Masayuki; Ikemoto, Yumiko; Kaneko, Kazunari (Pediatrics international, 2009)
Background:  Neutrophils of patients with Down syndrome (DS) are known to have numerous abnormalities associated with diminished resistance to infection. The intracellular calcium (Ca2+i) acts as a second messenger and regulates diverse functions in many cell types. The purpose of the present study was to compare the intracellular calcium concentration ([Ca2+]i) at baseline and stimulated conditions in DS patients and in normal subjects to investigate [Ca2+]i regulation in neutrophils. Methods:  The study group consisted of 27 subjects with DS (age, 8.6 ± 4.6 years) and 14 healthy subjects (age, 12.0 ± 3.9 years). Using a fluorescent probe, fura‐2, the baseline levels and changes in [Ca2+]i were examined after stimulation of neutrophils with N‐formyl‐methionyl‐leucyl‐phenylalanine (fMLP). Results:  At baseline, the [Ca2+]i of neutrophils from DS subjects was significantly higher than that of the controls (70.6  ±  28.0  nmol/L vs 44.4 ± 16.0 nmol/L, P < 0.01). The absolute [Ca2+]i after addition of fMLP in the DS subjects was also significantly higher than that of the control group (250 ± 91 nmol/L vs 167 ± 60 nmol/L, respectively: P < 0.01). The neutrophils from the DS subjects had a consistently and significantly prolonged response to fMLP as compared to the neutrophils of control subjects. Conclusions:  The higher [Ca2+]i and the prolonged response of [Ca2+]i to fMLP appear to be phenotypic traits of neutrophils in subjects with DS. This suggests intrinsic cellular defects in DS.